2015
DOI: 10.1159/000371760
|View full text |Cite
|
Sign up to set email alerts
|

Can Genomic Amplification of Human Telomerase Gene and C-MYC in Liquid-Based Cytological Specimens Be Used as a Method for Opportunistic Cervical Cancer Screening?

Abstract: Objective: To evaluate the effectiveness of five methods including the ThinPrep cytological test (TCT), liquid-based cytology, the human papillomavirus (HPV) test, detection of the TERC and C-MYC genes and visual inspection with acetic acid/Lugol's iodine (VIA/VILI) for opportunistic cervical cancer screening, and to explore whether genomic amplification of the human telomerase gene and C-MYC in liquid-based cytological specimens can be used as a method for opportunistic cervical cancer screening. Methods: Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The accuracy of TCT is the highest of the five screening methods (TCT, HPV test, detection of the TERC and C-MYC genes and visual inspection with acetic acid/Lugol's iodine [VIA/VILI]) for the diagnose of high-grade CIN [16]. A report showed that high-grade squamous intraepithelial lesions were a significant factor correlating with a positive endocervical margin and residual/recurrent disease in women with CIN who did not undergo hysterectomy [17].…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of TCT is the highest of the five screening methods (TCT, HPV test, detection of the TERC and C-MYC genes and visual inspection with acetic acid/Lugol's iodine [VIA/VILI]) for the diagnose of high-grade CIN [16]. A report showed that high-grade squamous intraepithelial lesions were a significant factor correlating with a positive endocervical margin and residual/recurrent disease in women with CIN who did not undergo hysterectomy [17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most cervical cancer screening is opportunistic. 4 Thus, more attention should be paid to the sensitivity and negative predictive value (NPV) during the postoperative period.…”
Section: Introductionmentioning
confidence: 99%
“…For example, TCT is only capable of identifying patients with abnormal cell morphology, and cannot determine if these patients are at high-risk of lesion progression. Additionally, the results of TCT may be influenced by sampling and slide quality, based on the skill and experience of the practitioner (8). It has also been reported that HPV infection is reversible in the reproductive system and only 1–2% of persistent HPV infections progress to neoplasia (9,10).…”
Section: Introductionmentioning
confidence: 99%